2018
DOI: 10.1093/dote/doy078
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy versus neoadjuvant chemoradiotherapy for cancer of the esophagus or gastroesophageal junction: long-term results of a randomized clinical trial

Abstract: NeoRes I is a randomized phase II trial comparing neoadjuvant chemoradiotherapy with neoadjuvant chemotherapy in the treatment of resectable cancer of the esophagus or gastroesophageal junction. Patients with biopsy-proven adenocarcinoma or squamous cell carcinoma, T1N1 or T2-3N0-1 and M0-M1a (AJCC 6th ed.), were randomized to receive three 3-weekly cycles of cisplatin 100 mg/m2 day 1 and fluorouracil 750 mg/m2/24 hours, days 1-5 with or without the addition of concurrent radiotherapy 40 Gy, 2 Gy/fraction, 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
130
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 17 publications
12
130
3
Order By: Relevance
“…show an clear link between pCR and short term survival, furthermore patients AC demonstrated a trend towards lower long-term survival, possibly as a result of mortality related to the treatment, and the opposite in patients with SCC (20). The same results were later observed in regard to long term survival where no significant differences were observed between the two treatment arms (21).…”
Section: Neoadjuvant Treatmentsupporting
confidence: 52%
“…show an clear link between pCR and short term survival, furthermore patients AC demonstrated a trend towards lower long-term survival, possibly as a result of mortality related to the treatment, and the opposite in patients with SCC (20). The same results were later observed in regard to long term survival where no significant differences were observed between the two treatment arms (21).…”
Section: Neoadjuvant Treatmentsupporting
confidence: 52%
“…In this cohort, although the postoperative pathology was considerably more favourable after NACRT, the rate of early recurrence was no less, and tended to be higher (NACRT 35·5 per cent, NACT 27·5 per cent; P = 0·061 ( Table S2 , supporting information)). This suggests that, although postoperative pathology is more favourable with NACRT, this does not translate to better outcome; hence ypT3 N1 R0 status after NACT does not have the same meaning as a ypT3 N1 R0 result after NACRT, at least in the early phase after treatment. This is important in postoperative discussions with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether neoadjuvant chemotherapy (NAC) is inferior in esophageal SCC compared to nCRT is yet unknown. The NeoRes trial with 181 AC and SCC patients compared NAC to nCRT but found no significant subgroup difference between histological subtypes [83]. Ongoing RCTs, like the Japanese NExT study (JCOG1109), will help elucidate if nCRT is preferred over NAC [131].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors for the curative treatment of esophageal cancer identified from OS multivariate analyses in at least one RCT. In total, there were 28 RCTs contributing to Figure 3 with 16 investigating neoadjuvant therapy [10,11,54,58,61,62,64,65,66,69,70,73,74,76,80,83], seven definitive chemoradiotherapy [57,60,71,72,75,82,98], three adjuvant therapy [67,77,79], and two radiotherapy alone [63,68]. * Potentially clinically relevant factors according to the criteria described in the method section.…”
Section: Figurementioning
confidence: 99%